Improving the Stability and Performance of Perovskite Light‐Emitting Diodes by Thermal Annealing Treatment. Issue 32 (30th May 2016) - Yu, Jae Choul; Kim, Dae Woo; Kim, Da Bin; Jung, Eui Dae; Park, Jong Hyun; Lee, Ah‐Young; Lee, Bo Ram; Di Nuzzo, Daniele; Friend, Richard H.; Song, Myoung Hoon
Abstract : A perovskite LED with a perovskite film treated under optimum thermal annealing conditions exhibits a significantly enhanced long‐term stability with full coverage of the green electroluminescence emission due to the highly uniform morphology of the perovskite film.